The Effect of European Integration on Swiss Energy Policy and Governance - van Baal, Paul Adrianus (2019)
The unique “Swiss way” of association with the European Union (EU) has received increasing attention in light of recent events such as Brexit as it is based on sectoral agreements without an overarching institutional framework. As such, Europeanization of Swiss domestic policy does not follow a straightforward process. We examine the external governance processes that drive the Europeanization of Swiss energy policy. Switzerland and the EU are highly interdependent in energy due to Switzerland’s geographical position but there is a relatively low level of policy alignment, as there is no formal EU-Swiss energy agreement nor has Switzerland autonomously implemented legislation equivalent to the EU energy acquis. The EU has fully liberalized the energy market and is focusing on consumer empowerment and decarbonization through the Clean Energy Package, whereas the Swiss energy sector remains only partially liberalized. Through a series of expert interviews with key stakeholders, we reconstruct the historical developments in Swiss energy policy, focusing on the relationship with, and the influence of the EU. We observe elements of each of the three ideal modes of governance—markets, hierarchies, and networks. The relative importance of these modes of coordination in governing EU-Swiss energy relations has shifted considerably over time. Gradual harmonization of EU energy markets and certain key events have driven Swiss exclusion from EU network governance processes, leading to more hierarchy. We identify the strengths and weaknesses of each mode of governance for EU-Swiss energy relations in their historical setting and discuss the implications for energy policy in Switzerland in the context of the Clean Energy Package and EU external relations in general.